STRATEGI BERTAHAN CAFE MELALUI PENDEKATAN INTEGRATED MARKETING COMMUNICATION DI MASA PANDEMI COVID-19 - Jihan Indah Sari; Joko Susilo (Jurnal Pustaka Komunikasi, 2021)
Covid-19 Pandemic  affects all sectors around the world, including economic sector especially in culinary bussines field. The impact of covid-19 is felt directly by bingsoo cafe, such as income has dropped  and there is no customer that comes by due to government's policy which forces people to stay at home. The purpose of this research is  to describe the  defensive strategy by bingsoo cafe through the approach of integrated marketing communications (IMC), so that it can continue to defense and adapt  to the bussines situation of Covid-19 pandemic. The method of this research is qualitative with observation technique and deep interview. The result of this research indicates that bingsoo cafe applies the strategy of Integrated Marketing Communications (IMC) by combining 9 out of 12 elements of promotion. Those elements are Advertising, Social Media And Website/Internet Marketing, Personal Selling, Public Relations, Sales Promotion, Point Of Sale And Merchandising, Corporate Identity, Packaging, And Word Of Mouth.